Spatial interdependence in cost efficiency and local government optimal size: The case of Italian municipalities. (April 2023) - Vidoli, Francesco; Auteri, Monica; Marinuzzi, Giorgia; Tortorella, Walter
Abstract: This study provides an original approach to empirically determine the optimal size of municipalities for efficient social service delivery in Italy, accounting for spatial spillover effects across municipalities as well as endogeneity between the output provided and its cost. A highly disaggregated and up-to-date database of Italian municipalities is used to estimate, through endogenous spatial frontier of Kutlu et al. (2020), the minimum costs. In municipalities with population ranging from 2000 to 3500 economies of scale in social service provision emerge, exhibiting cost-optimality. This outcome is completely ignored in some Regional government where financing criteria are based on historical, non-public, and ex-post repayment criteria. Highlights: Optimal size of municipalities in terms of cost efficiency. Within and between differences in regional social service delivery cost. Endogenous spatial frontier to account spatial spillover effects.